2012
DOI: 10.3390/en5020270
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on NOx Reduction by Primary Measures in Biomass Combustion: Straw, Peat, Sewage Sludge, Forest Residues and Wood Pellets

Abstract: An experimental investigation was carried out to study the NO x formation and reduction by primary measures for five types of biomass (straw, peat, sewage sludge, forest residues/Grot, and wood pellets) and their mixtures. To minimize the NO x level in biomass-fired boilers, combustion experiments were performed in a laboratory scale multifuel fixed grate reactor using staged air combustion. Flue gas was extracted to measure final levels of CO, CO 2 , C x H y , O 2 , NO, NO 2 , N 2 O, and other species. The fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 47 publications
7
49
1
Order By: Relevance
“…Previously, it had been suggested that the combustion of herbaceous biomass should be confined to larger combustion plants [3]. However, recent research work has shown that air staging can be successfully used to reduce emissions from the combustion of problematic fuels in small scale combustion systems [11,17]. Consequently, three air staging strategies (adjustment of primary air, adjustment of total excess air and adjustment of combustion temperature) were studied as potential means to reduce gaseous and particulate emissions from the combustion of four energy crops of relevance to Irish conditions (miscanthus, willow, tall fescue and cocksfoot) and wood.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it had been suggested that the combustion of herbaceous biomass should be confined to larger combustion plants [3]. However, recent research work has shown that air staging can be successfully used to reduce emissions from the combustion of problematic fuels in small scale combustion systems [11,17]. Consequently, three air staging strategies (adjustment of primary air, adjustment of total excess air and adjustment of combustion temperature) were studied as potential means to reduce gaseous and particulate emissions from the combustion of four energy crops of relevance to Irish conditions (miscanthus, willow, tall fescue and cocksfoot) and wood.…”
Section: Introductionmentioning
confidence: 99%
“…A similar trend was observed in Pleckaitine and Buinevicius's model (2011) [8], according to which conversion was expressed by the equation X NOx = 11.312 × (N K ) −0.6196 (where N K is the nitrogen content in fuel, expressed as a percentage). Another graphically similar shape was produced by laboratory measurements of biomass combustion in an electrically heated reactor, where obtained values were considerably lower than the generally recognized values [24]. It follows from this that the results of laboratory modeled experiments cannot always be used for accurate calculations in real practice.…”
Section: Discussionmentioning
confidence: 78%
“…Wood itself has very low nitrogen content (the three main components, cellulose, hemicellulose and lignin, contain no nitrogen at all). The nitrogen content of dry wood has been quantified [24] as 0.11%, thus the burning wooden crib would not be expected to contribute significantly to the HCN yield.…”
Section: Gas Concentrationsmentioning
confidence: 99%